Burden sharing in deficit countries: A questionnaire-experimental investigation - Wulf Gaertner; Lars Schwettmann (SERIEs - Journal of the Spanish Economic Association, 2017)
This paper studies the problem of burden sharing in countries that were forced to introduce severe budget cuts after the collapse of Lehman Brothers in 2008 which had unleashed a financial crisis in many industrialised countries of the Western world. We do not ask how the burden was actually split in each country examined but how the burden should have been shared among different income groups of society. In order to answer this question, a questionnaire-experimental investigation was run among students from Cyprus, Greece, Ireland, Italy, Portugal, and Spain. Our study offered the students seven different schemes of taxation amongst which we had specified a proportional rule and two progressive schemes of differing severity. A key result within our investigation is the finding that a large majority of students in all countries involved rarely opted for a proportional rule of burden sharing but picked one of the two progressive schemes instead. However, there were differences between countries with respect to the frequencies of these three rules, whereby Greece and Ireland were polar cases. The other rules received only minor support.
Keywords: D31; D63; D71; H24; 330; Burden sharing; Proportional rule; Progressive schemes; Questionnaire studies